2015
DOI: 10.1111/tbed.12394
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Potential Role of Pigs in the Epidemiology of Ebola Virus in Uganda

Abstract: Summary Uganda has experienced 4 Ebola outbreaks since the discovery of the virus. Recent epidemiological work has shown pigs are hosts for Ebola viruses. Due to their high reproduction rates, rapid weight gain, potential to provide quick financial returns and rising demand for pork, pig production in Uganda has undergone massive expansion. The combination of pork sector growth supported by development programmes and Ebola virus risk prompted a foresight exercise using desk, interview and spatial methods. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
(46 reference statements)
0
18
0
1
Order By: Relevance
“…The four sampling periods coincided with times when the number of pigs being processed was known to increase to meet pork demand during holiday times. 35 Findings reported here were part of a larger study designed to demonstrate proof of freedom from filoviruses. Thus, samples from 649 pigs were available for detection of bacterial pathogens in the present study.…”
Section: Methodsmentioning
confidence: 95%
“…The four sampling periods coincided with times when the number of pigs being processed was known to increase to meet pork demand during holiday times. 35 Findings reported here were part of a larger study designed to demonstrate proof of freedom from filoviruses. Thus, samples from 649 pigs were available for detection of bacterial pathogens in the present study.…”
Section: Methodsmentioning
confidence: 95%
“…Subsequent experimental infection of pigs with Ebola virus (EBOV) confirmed susceptibility of pigs to this highly pathogenic virus which resulted in clinical symptoms, oronasal shedding as well as transmission to co‐housed piglets and non‐human primates (Kobinger et al, ; Weingartl et al, ). In addition, a more recent study identified several factors such as domestic pig habitat overlap with assumed wildlife reservoir hosts as well as reported human–pig–wildlife interactions that might contribute to potential zoonotic transmission of ebolaviruses from pigs under field conditions (Atherstone, Smith, Ochungo, Roesel, & Grace, ). Overall, serological field studies investigating pigs for the presence of ebolavirus‐specific antibodies are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…The Democratic Republic of Congo's total consumption of pork is expected to increase by 100%, Tanzania by 32%, and Kenya by 25% between 2000 and 2030 (Food and Agriculture Organization 2011). Introduction and expansion of pig production systems in these biodiverse landscapes may create new risks, including pathogen transfer from pigs to humans (Ocaido et al 2013;Wilson 2017;Food and Agriculture Organization (FAO) 2012; Atherstone et al 2015;Hamill et al 2013; Electronic supplementary material The online version of this article (https://doi.org/10.1007/s11250-018-1668-6) contains supplementary material, which is available to authorized users. Agriculture Organization 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Agriculture Organization 2017). Of particular public health interest is the role of pigs in the zoonotic transmission of emerging pathogens to people (Atherstone et al 2015;Vergara-Alert et al 2017;Middleton and Westbury 2002;Ma et al 2008;Kobinger et al 2011;Conlan et al 2012;McCormack and Allworth 2002;AbuBakar et al 2004;Marsh et al 2011). As pig traders form an important link between pig farms and pork customers, research informing their knowledge, attitudes, and practices is essential.…”
Section: Introductionmentioning
confidence: 99%